The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.ijmedinf.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Automated problem list generation and physicians perspective from a pilot study

Abstract: Cognitive computing systems like this Watson system hold the potential for accurate, problem-list-centered summarization of patient records, potentially leading to increased efficiency, better clinical decision support, and improved quality of patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“… 12 , 17 , 18 From an interventional perspective, clinical decision support tools, automated alerts, and machine learning may play a role in improving problem list completeness across a wide range of diseases. 19–21 …”
Section: Introductionmentioning
confidence: 99%
“… 12 , 17 , 18 From an interventional perspective, clinical decision support tools, automated alerts, and machine learning may play a role in improving problem list completeness across a wide range of diseases. 19–21 …”
Section: Introductionmentioning
confidence: 99%
“…Such solutions include note templates, such as that provided by Epic SmartPhrases (Epic Systems Corporation, Verona, Wisconsin, Unites States), 30,31 strategic menu design, 32,33 and order sets. 34 Automationcentric innovations also exist, such as automated problem list generation 35 and follow-up determination after radiographic testing, 36 as well as clinical decision support, alerts for risk stratification 37 and drug-disease interactions. 38 A study by Arndt et al of ambulatory family practitioners in the United States showed that clinicians devote nearly 50% of their total daily time in their EHR performing clinical documentation and chart review, with chart review comprising nearly 75% of EHR tasks related to direct medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that the electronic problem list is often incomplete. 6 7 Some studies have explored making the problem list more complete by using natural language processing, 14 importing claims data, 15 or implementing rules based on structured data or decision support tools. 16 17 …”
Section: Discussionmentioning
confidence: 99%